Community Pharmacists’ Views of the Enforced Antibiotics Dispensing Law and Its Impact on Oral Antibiotics Sales in Saudi Arabia - AlRukban M; AlRuthia Y; Almasaoud M; Al-Owairdhi M; Alsouan A; Alrabiah A; Alshaikh A; Alsuhaibani A; Aleidan A (Dove Medical Press, 2020)
Mohammed AlRukban,1,* Yazed AlRuthia,2,3,* Majed Almasaoud,4 Mohammad Al-Owairdhi,5 Anwar Alsouan,4 Abdullah Alrabiah,4 Abdulrahman Alshaikh,4 Adel Alsuhaibani,4 Alan Aleidan4 1Department of Family Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Pharmacoeconomics Research Unit, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 4College of Medicine, King Saud University, Riyadh, Saudi Arabia; 5Department of Pharmacoeconomics and Drug Pricing, Saudi Food and Drug Authority, Riyadh, Saudi Arabia*These authors contributed equally to this workCorrespondence: Yazed AlRuthia Tel +996114677483Fax +966114677480Email yazeed@ksu.edu.saObjective(s): The aim of this study was to explore community pharmacists’ views toward the antibiotics dispensing law that was enforced in May 2018 and bans the sale of antibiotics without a prescription in community pharmacy settings in Saudi Arabia. Moreover, the potential impact of the law enforcement on the sales of oral antibiotics in Saudi Arabia was also explored.Methods: A questionnaire-based cross-sectional study was conducted between September 2019 and March 2020 in Riyadh, Saudi Arabia. A multistage sampling technique was used to recruit community pharmacists from different districts. Pharmacists who consented to participate and reported practicing prior to the law enforcement were interviewed about their views of the law using a 14-item newly developed questionnaire. The annual sales of oral antibiotics for the years of 2017, 2018, and 2019 were retrieved from the Saudi Food and Drug Authority (SFDA) database.Results: Two hundred and eighty six pharmacists consented to participate and met the inclusion criteria. After the law enforcement, approximately 51% of the participants reported that the percentage of patients seeking antibiotics without a prescription is less than 25%. Moreover, the majority (87.41%) reported a drop in the sales of antibiotics. Additionally, about 90% of the participants believed that the rate of inappropriate use of antibiotics will decrease as a result of the law enforcement. About 41% of the participants reported that the law has negatively impacted their pharmacies’ profits. The sales of oral antibiotics have seen a 16.6% drop in the year of 2019 as compared to 2017.Conclusion: The antibiotics dispensing law is favorably perceived among community pharmacists in Saudi Arabia despite some concerns about its impact on their sales. Exploring different business models that delink the profits from the volume of antibiotics sales is necessary for this vital industry to thrive.Keywords: antibiotics, drug resistance, community pharmacy, sales, Saudi Arabia